A Slippery, Changing Concept: How Korean New Religions Define Religion - Baker, Don (Journal of Korean religions, 2010)
The term “religion” is relatively new to Korea, having being introduced at the end of the 19th century. Since it is an imported term, it still is a rather loose fit for the various organizations and phenomena in Korea that outsiders often label as religious, since not all such organizations or phenomena meet all of the criteria often used to determine what is and what is not religious. Moreover, governments in Korea have often tried to limit the religion label to “respectable” religions, those with organizational structures that made them more amenable to government control. At the same time, many new religions have tried to avoid the religion label because they see it as implying an exclusive rather than an inclusive community. Religion, therefore, remains a problematic term in Korea, lacking agreement regarding how it should be applied.